KEHARMONISAN KELUARGA MUSLIM DI ERA MEWABAHNYA PENGARUH GAME ONLINE DI KELURAHAN BUNUT BARAT - Dasopang, Mara Ikhlas; Siagian, Nilasari; ., Zaleha (Jurnal Ushuluddin, 2023)
Harmony in the household actually depends on the closeness of the relationship between all family members, including the relationship between husband and wife, parents and children, and between siblings. Each individual in the family has a responsibility to maintain the balance of relationships with each other. Background in this problem, How is the condition of the family using online games in the Household, Household Harmony, analysis of Muslim family harmony in the era of the spread of online games. Research results and discussions on the impact of an online game on household harmony. Online games are one of the causes of the loss of household harmony, which used to be a harmonious, peaceful and peaceful household, but are destroyed by online games. Household Harmony whose husband is addicted to online games, Online games are also one of the causes of infidelity, an online game player meets the opposite sex through online games. until starting from the online game they are comfortable with each other and feel compatible so that the online game becomes a reason for them to meet, so that after meeting they feel comfortable and compatible with each other so that an affair occurs.